Peningkatan Mutu Pendidikan Melalui Sistem Automasi Akreditasi Nasional Sekolah/ Madrasah - Kautsar, Akbarul (Jurnal Aktual Pendidikan Indonesia, 2022)
The aim of the research is to improve the quality of education through the School/Madrasah National Accreditation Automation System, the research method is to use library research. The S/M accreditation program is one of several series of implementation of the educational process as a whole. The S/M accreditation automation program must be developed in line with technological developments. The industrial revolution 4.0 made it possible for a conventional bureaucratic system to become an electric bureaucracy system (e-bureaucracy). One of them, with the widespread use of big data, is very possible to produce an accurate statistical model in predicting a decision outcome. This system works automatically and makes decisions based on statistical modeling to predict the value of S/M accreditation. This method can work more optimally with big data to gain insight so that the system can make decisions accurately. Improving the quality of education through the implementation of S/M accreditation by integrating ICT is a breakthrough for making savings and increasing time efficiency. The digitization process by utilizing big data is believed to be able to improve model statistics in making accurate decisions. Therefore, the accreditation automation system can be a solution in improving the quality of national education.